Factors affecting performance in an ultraendurance triathlon - Laursen, P. B.; Rhodes, E. C. (Sports Medicine, 2001)
In the recent past, researchers have found many key physiological variables that correlate highly with endurance performance. These include maximal oxygen uptake (VO2max), anaerobic threshold (AT), economy of motion and the fractional utilisation of oxygen uptake (VO2). However, beyond typical endurance events such as the marathon, termed 'ultraendurance' (i.e. >4 hours), performance becomes harder to predict. The ultraendurance triathlon (UET) is a 3-sport event consisting of a 3.8 km swim and a 180 km cycle, followed by a 42.2 km marathon run. It has been hypothesised that these triathletes ride at approximately their ventilatory threshold (Tvent) during the UET cycling phase. However, laboratory assessments of cycling time to exhaustion at a subject's AT peak at 255 minutes. This suggests that the AT is too great an intensity to be maintained during a UET, and that other factors cause detriments in prolonged performance. Potential defeating factors include the provision of fuels and fluids due to finite gastric emptying rates causing changes in substrate utilisation, as well as fluid and electrolyte imbalances. Thus, an optimum ultraendurance intensity that may be relative to the AT intensity is needed to establish ultraendurance intensity guidelines. This optimal UET intensity could be referred to as the ultraendurance threshold.